PENINGKATAN PROFESIONALISME GURU PAUD DALAM PELAKSANAAN KURIKULUM 2013 REVISI (Studi Kasus di Kober Az Zahra dan Kober Mutiara di Kabupaten Tasikmalaya) - Ida Ratnaningsih, Ida Ratnaningsih; Ujang Cepi Barlian, Ujang Cepi Barlian; Yosal Iriantara, Yosal Iriantara (JISOS: JURNAL ILMU SOSIAL, 2022)
The level of professionalism of PAUD teachers is still very low, it can be seen from the academic qualifications and competencies possessed by PAUD teachers themselves, especially in rural areas. The purpose of the study was to examine and analyze to determine the increase in the professionalism of PAUD teachers in implementing the 2013 revised edition of the curriculum in designing and implementing learning and evaluating learning outcomes. Planning is carried out with systematic preparation of an activity carried out through meetings of foundations, principals and teachers to determine the objectives of implementation and evaluation of learning as outlined in the curriculum document. Promises refer to annual programs that have been created and fostered by the school curriculum team, RPPH and RPPM are made and compiled by teachers periodically and adjusted to the theme of the activity. Organizing is carried out in the division of tasks or grouping materials, programs and media that will be planned in learning. Motivation is given before playing, during playing, and after playing. Teacher supervision is carried out directly by the principal and PAUD supervisors from the official element to monitor the implementation of KBM and teacher performance evaluation is carried out during the learning process and after learning is complete by filling out the teacher assessment sheet form. Assessment or evaluation is carried out by each teacher according to the progress of the evaluation carried out to determine the achievement of the basic competencies that have been planned and determined.